Efficiency and Determinants in Libyan Banks - Alrafadi, Khalad (Archives of Business Research, 2020)
This paper provides a comparative analysis regarding the performance of 17 Libyan banks over the period 2004 up to 2010. According to the relevant literature, there are few studies that combine both the Data Envelopment Analysis (DEA) technique and Tobit model for assessing the efficiency levels and subsequently examining the determinants of efficiency for the banking sector in Libya. For this study, the DEA technique was used to estimate cost, allocative, and technical efficiency of sampled banks by using DEAP software. In the second stage, Tobit regression model was used to identify potential determinants of efficiency by using Stata10 software. The results showed that the specialized banks have exhibited higher mean cost efficiency relative to commercial and private banks. The results of efficiency determinants showed positive relationship between bank efficiency, and return on investment (ROA); risk; and size of operation (SO). This paper concludes with some policy implications of the results.